ENGAGING STUDENTS IN EXTENSIVE READING THROUGH LITERARY TEXTS IN THE EFL CLASSROOM - Loh Chin Ee (Universitas Negeri Padang, 2016)
Much has been written about the benefits of extensive reading, which include increased positive attitudes towards reading, increased scores in reading comprehension ability and increased reading speed and fluency. Well-implemented extensive reading programmes can thus improve students’ reading competency and motivate them to read more. As a result of their wide reading, they are more likely to increase their knowledge, which lead greater linguistic and academic competence. This paper argues for the use of literary texts to engage students in extensive reading in the EFL classroom. In addition to improving their linguistic ability, the students are exposed to creativity in language, to different social and culture worlds embedded in texts, and to enjoyment through the reading of literature. Various strategies for using literary texts such as reading aloud, organizing literary reading circles, complementing extensive reading with intensive reading of literary texts, book cluster selection will be discussed in this paper.